Systemic absorption of triamcinolone acetonide is increased from intrasynovial versus extrasynovial sites and induces hyperglycemia, hyperinsulinemia, and suppression of the hypothalamic-pituitary-adrenal axis - Hallowell, Kimberly L.; Dembek, Katarzyna; Horne, Caitlyn R.; Knych, Heather K.; Messenger, Kristen M.; Schnabel, Lauren V. (Frontiers in Veterinary Science, 2024)
Steroid-associated laminitis remains a major concern with use of corticosteroids in horses. Individual case factors such as joint pathology, pre-existing endocrinopathies, or corticosteroid type, dose, and timing influencing steroid-induced laminitis risk have not been investigated. This study aimed to determine if systemic absorption of triamcinolone acetonide (TA) varies between intrasynovial (antebrachiocarpal) and extrasynovial (sacroiliac) injection sites, and to determine the effects of TA absorption on glucose, insulin, cortisol, and adrenocorticotropic hormone (ACTH). Twenty adult horses were randomized into antebrachiocarpal or sacroiliac joint injection groups, and each horse received bilateral injections with a total dose of 18 mg triamcinolone. Blood was collected prior to injection and at 1, 2, 4, 6, 8, 10, 12, 16, 20, 24, 36, 48, 60, and 72 h post-injection. Peak TA absorption occurred at 8 h in both groups, and was significantly higher in the intrasynovial group compared to the extrasynovial group (1.397 ng/mL, 0.672 ng/mL, p < 0.05). Plasma TA levels were significantly higher in the intrasynovial group from 8 to 36 h post-injection (p < 0.05). There was no difference in glucose, insulin, cortisol, or ACTH between groups at any time point. Insulin and glucose were significantly increased from baseline at all timepoints from 10–72 h and 1–72 h post-injection, respectively. Horses with elevated baseline insulin values (>20 μU/mL) from both groups experienced a more marked hyperinsulinemia, reaching a mean peak insulin of 197.5 μU/mL as compared to 90.06 μU/mL in those with normal baseline insulin. Cortisol and ACTH were significantly decreased from baseline at timepoints from 4–72 h post-injection in both groups. This study is the first to evaluate drug absorption from the sacroiliac site and demonstrates that drug absorption varies between intrasynovial and extrasynovial injection sites. TA absorption causes metabolic derangements, most notably a marked hyperinsulinemia that is more severe in horses with elevated baseline insulin values. The influence of baseline endocrinopathies on response to corticosteroid administration as well as the effect of corticosteroid-induced metabolic derangements warrant further investigation as risk factors for corticosteroid-associated laminitis.